The effect of pressure, opportunity, rationalization, capability, arrogance, and collusion on fraudulent financial statement - Az Zahra, Shifa Nurhaliza; Irawan, Ferry (WIM Solusi Prima, 2025)
The financial statement provides financial information presented by a company for a specific period to assess its financial condition, capabilities, and operational performance. This information is valuable for both external and internal stakeholders. Thus, it is crucial for financial statements to be presented accurately and free from errors. However, manipulation or fraud in financial reporting remains a common issue. This study examines fraudulent financial statement in state-owned enterprises (BUMN) from 2018 to 2022 using the hexagon fraud theory. A quantitative approach is employed, utilizing secondary data from annual reports. The study uses 100 data from 20 companies selected through purposive sampling over the 2018–2022 period. Data were analyzed using panel data analysis with STATA software. The findings indicate that pressure (X1), opportunity (X2), rationalization (X3), arrogance (X5), and collusion (X6) have no significant effect on fraudulent financial reporting, while capability (X4) has a significant negative effect.